Use of the BD PHOENIX Automated Microbiology System for Direct Identification and Susceptibility Testing of Gram-Negative Rods from Positive Blood Cultures in a Three-Phase Trial - Funke, Guido (American Society for Microbiology, 2004)
The present study describes the use of the automated BACTEC 9240 blood culture system, the Serum Separator Tube (SST), and the BD PHOENIX Automated Microbiology System in combination for the direct identification and antimicrobial susceptibility testing (AST) of gram-negative rods (GNRs) from positive blood cultures (BCs) without subculture. The study was conducted in three phases: (i) the recovery yield of Escherichia coli ATCC 25922 was determined with the SST between 0 and 8 h after spiked BC bottles turned positive; (ii) the identifications and susceptibility testing results obtained with the PHOENIX system for nine American Type Culture Collection strains of GNRs processed by the SST procedure and for colonies from agar medium were compared; and (iii) the procedure with the BACTEC system, SSTs, and the PHOENIX system was applied to positive cultures of blood from 309 patients during a 3-month period. The SST procedure with E. coli yielded sufficient numbers of cells to perform direct inoculation at any time between 0 and 8 h after a BC bottle turned positive. By using the identities obtained from pure cultures with the PHOENIX system and other biochemical identification systems as reference methods, the agreement between the reference methods and the PHOENIX system tested directly by using cultures of blood from patients was 92.9%. The 7.1% discrepant results were due to 6.5% incorrect identifications with the PHOENIX system with BC samples and 0.6% incorrect identifications with the PHOENIX system with samples from agar cultures. By AST the overall categorical accuracy was 99.0%, with 0.1% very major errors, 0.1% major errors, and 0.8% minor errors. In conclusion, use of the combination of the BACTEC system, SSTs, and the PHOENIX system has the potential to allow the agar isolation step to be skipped and the procedures for rapid direct identification and susceptibility testing of GNRs from positive BCs to be improved both in hospital-based and in central non-hospital-based laboratories.